2015
DOI: 10.3892/ijmm.2015.2113
|View full text |Cite
|
Sign up to set email alerts
|

Berberine regulates melanin synthesis by activating PI3K/AKT, ERK and GSK3β in B16F10 melanoma cells

Abstract: Berberine, an isoquinoline alkaloid, has a wide range of beneficial properties, including anti-bacterial, anti-inflammatory, anti-cancer, and cholesterol-lowering effects. Recently findings suggest that berberine improves glucose and lipid metabolism disorders. In the present study, we examined the mechanism underlying the inhibitory effect of berberine on α-melanocyte-stimulating hormone (α-MSH)-stimulated B16F10 melanoma cells. The results showed that berberine attenuated α-MSH induction of the microphthalmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Aside from its traditional use as a treatment for gastrointestinal disorders, BBR has been demonstrated to exhibit inhibitory functions in a number of additional diseases, including cancer (2), microbial infection (3), inflammatory and autoimmune diseases (such as cardiovascular disease) (4), collagen-induced arthritis (5), experimental type I diabetes in mice (6) and experimental autoimmune encephalomyelitis (EAE) (7). Numerous reports have demonstrated that BBR may suppress the Th17 response in certain autoimmune diseases (68).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from its traditional use as a treatment for gastrointestinal disorders, BBR has been demonstrated to exhibit inhibitory functions in a number of additional diseases, including cancer (2), microbial infection (3), inflammatory and autoimmune diseases (such as cardiovascular disease) (4), collagen-induced arthritis (5), experimental type I diabetes in mice (6) and experimental autoimmune encephalomyelitis (EAE) (7). Numerous reports have demonstrated that BBR may suppress the Th17 response in certain autoimmune diseases (68).…”
Section: Introductionmentioning
confidence: 99%
“…While best known for antimicrobial, antiinflammatory, anti-hyperglycemic, and anti-hyperlipidemic effects [131], berberine is one of the most active alkaloids in melanoma. It has been shown to inhibit kinases like PI3K, ERK, and GSK3β [132]. Moreover, in combination with doxorubicin, it intensely reduces proliferation and increases apoptosis, effect demonstrated both in vitro and in vivo [133].…”
Section: Alkaloidsmentioning
confidence: 99%
“…Nutrients that affect PI3K/Akt pathway include water, proteins, carbohydrates, and fats (Table 2 ). Hypo-osmotic [ 46 48 ] or hyper-osmotic stresses [ 49 52 ] associated with disorders in water homeostasis are known to involve the PI3K/Akt signaling. Non-denatured and denatured proteins can activate PI3K/Akt.…”
Section: Dietary and Pharmacological Considerations That Influence Gsmentioning
confidence: 99%
“… Despite inducing the p21-activated serine-threonine kinase, requiring PI3K activation, within 30-min, hyper-osmotic stress suppresses melanin production that also requires PI3K activation, for days of the treatment, suggesting overstimulation of the PI3K/Akt pathway. [ 5 , 49 52 ] Proteins Non-denatured protein Male SD rats, human embryonic kidney cells. Branched-chain amino acids in cow milk are highly insulinotropic and a potent activator of PI3K/Akt.…”
Section: Dietary and Pharmacological Considerations That Influence Gsmentioning
confidence: 99%
See 1 more Smart Citation